Ponatinib and blinatumomab for Philadelphia chromosome-positive acute lymphoblastic leukaemia: a US, single-centre, single-arm, phase 2 trial. Issue 1 (January 2023) - Jabbour, Elias; Short, Nicholas J; Jain, Nitin; Huang, Xuelin; Montalban-Bravo, Guillermo; Banerjee, Pinaki; Rezvani, Katayoun; Jiang, Xianli; Kim, Kun Hee; Kanagal-Shamanna, Rashmi; Khoury, Joseph D; Patel, Keyur; et al.
Summary: Background: Ponatinib and blinatumomab are effective therapies in patients with Philadelphia chromosome-positive (Ph-positive) acute lymphoblastic leukaemia, and their combination might be a promising treatment option. In this study, we aimed to evaluate this chemotherapy-free strategy. Methods: We did a single-centre, single-arm, phase 2 study at the University of Texas MD Anderson Cancer Center, Houston, TX, USA, in patients aged 18 years or older with newly diagnosed or relapsed or refractory Ph-positive acute lymphoblastic leukaemia or chronic myeloid leukaemia in lymphoid blast phase. Patients with an ECOG performance status of 2 or less who had a total bilirubin concentration two-times the upper limit of normal (ULN) or less (≤2·4 mg/dL), alanine aminotransferase and aspartate aminotransferase concentration no more than three-times the ULN, and serum lipase and amylase concentrations no more than three-times the ULN were eligible for inclusion. Ponatinib 30 mg orally and continuous intravenous blinatumomab 28 μg over 24 h (for 28 days each cycle) were given in combination for up to five 42-day cycles, followed by ponatinib monotherapy. Patients received 12 doses of intrathecal chemotherapy as CNS prophylaxis. The primary endpoints were complete molecular response (defined as absence of a detectable BCR – ABL1 transcript by PCR at a sensitivity of 0·01%) in patients with newly diagnosed disease and overall response in patients with relapsed or refractory disease or chronic myeloid leukaemia in lymphoid blast phase. All assessments were done according to the intention-to-treat principle. The trial completed its original target accrual and was amended on March 23, 2022, to enrol an additional 30 patients, thus increasing the sample size to 90 patients. The trial is registered with ClinicalTrials.gov, NCT03263572, and it is ongoing. Findings: Between Feb 6, 2018, to May 6, 2022, 60 (83%) of 72 patients assessed were enrolled and received ponatinib and blinatumomab (40 [67%] patients had newly diagnosed Ph-positive acute lymphoblastic leukaemia, 14 [23%] had relapsed or refractory Ph-positive acute lymphoblastic leukaemia, and six [10%] had chronic myeloid leukaemia in lymphoid blast phase). 32 (53%) patients were men and 28 (47%) were women; 51 (85%) patients were White or Hispanic; and the median age of participants was 51 years (IQR 36–68). The median duration of follow-up for the entire cohort was 16 months (IQR 11–24). Of patients with newly diagnosed Ph-positive acute lymphoblastic leukaemia, 33 (87%) of 38 evaluable patients had a complete molecular response. 12 (92%) of 13 evaluable patients with relapsed or refractory Ph-positive acute lymphoblastic leukaemia had an overall response. 11 (79%) had a complete molecular response. Five (83%) of six patients with chronic myeloid leukaemia in lymphoid blast phase had an overall response. Two (33%) had a complete molecular response. The most common grade 3–4 adverse events that occurred in more than 5% of patients were infection (22 [37%] patients), increased amylase or lipase concentration (five [8%] patients), increased alanine aminotransferase or aspartate aminotransferase concentration (four [7%] patients), pain (four [7%] patients), and hypertension (four [7%] patients). One (2%) patient discontinued blinatumomab due to tremor. Three (5%) patients discontinued ponatinib secondary to cerebrovascular ischaemia, portal vein thrombosis, and coronary artery stenosis in one patient each. No treatment-related deaths were observed. Interpretation: The chemotherapy-free combination of ponatinib and blinatumomab resulted in high rates of complete molecular response in patients with newly diagnosed and relapsed or refractory Ph-positive acute lymphoblastic leukaemia. Patients with newly diagnosed Ph-positive acute lymphoblastic leukaemia could be spared the toxicities associated with chemotherapy and the need for allogeneic haematopoietic stem-cell transplantation in first response. Funding: Takeda Oncology and Amgen.